2019
DOI: 10.1111/and.13430
|View full text |Cite
|
Sign up to set email alerts
|

Are predictive factors in sperm retrieval and pregnancy rates present in nonobstructive azoospermia patients by microdissection testicular sperm extraction on testicle with a history of orchidopexy operation?

Abstract: The aim in this study is to evaluate predictive factors on sperm retrieval and pregnancy rates by microdissection testicular sperm extraction in non obstructive azoospermia patients with a history of orchidopexy operation. A total of 148 patients were included, and their medical files were evaluated. Data related to possible predictive factors on sperm retrieval and pregnancy rates such as age at orchidopexy operation, unilateral or bilateral presence of undescended testis before orchidopexy, testis volumes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Ozan et al showed a pregnancy rate of 28% after ICSI in accordance with the literature. They also demonstrated that the age at which patients underwent orchidopexy and the side on which cryptorchidism occurred had no significant effect on pregnancy rates after ICSI 9 . In the present study, younger male and female ages, and higher fertilization rates were the parameters that might predict pregnancy.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Ozan et al showed a pregnancy rate of 28% after ICSI in accordance with the literature. They also demonstrated that the age at which patients underwent orchidopexy and the side on which cryptorchidism occurred had no significant effect on pregnancy rates after ICSI 9 . In the present study, younger male and female ages, and higher fertilization rates were the parameters that might predict pregnancy.…”
Section: Discussionsupporting
confidence: 56%
“…9 They found sperm retrieval rate as 60%, and age at orchidopexy and the unilateral or bilateral presence of cryptorchidism have no correlation with sperm retrieval and pregnancy rates after the TESE. 9 In our series, younger male and female ages and higher fertilization rates were the parameters that might predict pregnancy. Laterality of the undescended testes (unilateral: 56.8% versus bilateral: 50.5%) did not differ in terms of pregnancy rate.…”
Section: F I G U R E 3 Relationship Between Serum Total Testosterone mentioning
confidence: 54%
See 3 more Smart Citations